Where are the women in women's sports? Predictors of female athletes' interest in a coaching career - Moran-Miller, K.; Flores, L. Y. (Research Quarterly for Exercise and Sport, 2011)
In this study, we used social cognitive career theory (Lent, Brown, & Hackett, 1994) to examine the development of female athletes' career interest in coaching and, specifically, the impact of contextual factors (female coaching role models, working hours, and perceived discrimination) on coaching self-efficacy and outcome expectations. Participants were 205 predominantly White, heterosexual female student athletes. A path analysis indicated that role models and working hours predicted coaching self-efficacy, which predicted coaching outcome expectations. Additionally, coaching self-efficacy, coaching outcome expectations, and contextual factors predicted coaching interest. Practical implications are discussed as well as suggestions for further research in this relatively unexplored area.